(untitled) (Caderno de Ciências Agrárias, 2024)
This study aimed to characterize the pulp of the tarumã fruit, harvested at different stages of maturation (immature and mature), in terms of physicochemical parameters and mineral content, and also to evaluate the bioactive com- pounds of the powdered pulp of the fruits, through analysis of phenolic compounds, antioxidant capacity (DPPH and ABTS) and anti-inflammatory activity. There was an increase (p≤0.05) in the pH, in the Ratio (soluble solids/titra- table acidity) and in the sugar levels during the maturation of the tarumã fruits. The powdered pulp showed a more intense red color (a*) when was mature, due to the degradation of chlorophyll and the synthesis of anthocyanins that occur during fruit ripening. Among the minerals evaluated, relevant concentrations of potassium were detected in the fruit pulp, and in ripe fruits, the concentration was even higher (p≤0.05). The values of total phenolic compounds, antioxidant activity (for both evaluated methods) and anti-inflammatory activity were higher in aqueous extracts of immature fruits. The tarumã can be a promising source of bioactive compounds, mainly the immature fruits, which showed the best results, while the ripe fruits can be used as raw material for fermentation processes, or for the pro- duction of natural dyes due to their intense purple color